Income Composition and Redistribution in Germany: The Role of Ethnic Origin and Assimilation - Felix Büchel; Joachim R. Frick (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper deals with the relative economic performance of immigrants compared to the native born population in Germany. We compare pre and post-government income, using data from the German Socio-Economic Panel from 1995 to 1997. We categorize six population subgroups by the ethnicity of the adult household members: native-born West Germans, East Germans, "pure" Aussiedler (ethnic German immigrants), "pure" non-ethnic German foreign immigrants, and "mixed" immigrants, either Aussiedler or foreign, living with an adult native-born German. Our results show that immigrants are quite heterogeneous with respect to their economic performance but, overall, non-ethnic German immigrants are net payers to the social security system. The two subgroups substantially benefiting from the income redistribution are "pure" Aussiedler and East Germans. By this measure, immigrants of non-German nationality are not an economic burden to the native-born population.
Keywords: 330; Einkommen; Soziale Integration; Einkommensumverteilung; Deutschland; Migranten; Aussiedler